Analisis Kurikulum pada Sistem Pendidikan Sekolah Dasar di Indonesia dan Jepang - Ni Wayan Risna Dewi; Ni Luh Ika Windayani; Bestari Laia; Putu Kerti Nitiasih; Putu Nanci Riastini (Cetta: Jurnal Ilmu Pendidikan, 2023)
Indonesia and Japan have different elementary school curriculum structure policies. This research aims to analyze the structure and implementation of the Japanese curriculum which has been proven to be effective in producing outcomes. The research method used is a literature review with a comparative descriptive study type of research. The data used in this research was obtained from primary and secondary library sources to obtain information and descriptions of research that had been conducted previously. Next, the data obtained is collected, analyzed and concluded to obtain results regarding the literature study. The results of the analysis carried out found similarities and differences in the structure of elementary school education in Indonesia and Japan. This can be assessed from educational policies, learning methods, curriculum structure and character development contained in the curriculum.